تحديد مستوى مؤشر معدل الطاقة القلبية للأشخاص الاصحاء والمصابين بالضغط الانقباضي والانبساطي - التميمي, امال صبيح سلمان; الجبوري, هيثم محمد كاظم (Sulaimani Journal for Humanities, 2018)
The research includes five doors as eating two researchers in the first section provided and the importance of research and discussed the importance of physiology because of this science from a prominent and significant role of the mother and that any weakness in the potential of functional appliances and of index cardiac energy rate will affects the efficiency of the heart and circulatory مجلة )زانکۆی سلێمانی( القسم )B )للدراسات االنسانیة – العدد )65( عدد خاص لمؤتمر الدولي األول لكلیة التربیة الرياضية 1301 system, which reflected negatively the health of the people on one hand and being unable to exercise daily their business well on the other hand, as well as the first door contains a research problem which focused on the lack of interest in functional devices, which are concentrated on the importance and the possibility of heart device and the power exerted by and blood paid the right ventricle to the lungs amount left ventricle into the aorta per minute during exercise of different activities or exercise daily business that needs a healthy heart, as well as to adapt the work of functional devices to do business and see people who enjoy good-powered attack for people who suffer from rising or falling pressure and do not have a heart card good so Arta researchers study this problem, either Part II theoretical studies have included it dealt researchers clarify the concept of cardiac energy and its importance rate index, measured and the concept of systolic and diastolic pressure and methods of measurement third Amaalabab of the research contained on research methodology and field procedures and a description of the community as a descriptive approach adopted either the research sample was It consisted of (30) were males aged (30-45 years), as well as the search variables and the most important procedures used as well as statistical methods Part IV has included a display reached by researchers from the results discussed so based on a range of scientific sources, either the door fifth reunion conclusions, recommendations, sources and references.